Evaluación De La Eficacia Del Implante Coclear En Función De La Edad De Implantación - Alegre, O. M; Rodríguez, M. C; Villar, L. M; Pérez, D (European Scientific Journal, ESJ, 2016)
Introduction and objective: Childhood hearing loss affects cognitive, emotional and language development of children causing difficulties in communication. Therefore, many organizations stress the importance of early detection of hearing loss and early cochlear implantation. The purpose was to verify the effect of cochlear implants performed in children from Tenerife (sorted by chronological age, age at cochlear implantation and time of use of cochlear implant) in lexical comprehension and communication skills. Method: A psycholinguistic profile of all children implanted in the province of Santa Cruz de Tenerife during the years 2007-2012 using two standardized tests were developed: The Illinois Test of Psycholinguistic Abilities (ITPA) and the Picture Vocabulary Test (Peabody). Results: Most of the children studied were implanted at a late age (over 3-yearolds). This situation carries some functional use of the implant but causes an indiscernible development of oral communicative functions of children. Specifically, 20% of the sample (28 children) was implanted with less than 2- year-olds; another 28% of children was implemented between the ages of 2 and 3 years old; finally, 58% of children was implemented with more than 3- year-olds. The latter age of implantation may affect the standard language development. Conclusions: This study has become evident that early implantation has a positive effect on language development of deaf children.